Pengaruh Strategi Komunikasi Dakwah terhadap Peningkatkan Minat Beribadah Dan Keterlibatan Pelajar Dalam Kegiatan Rohis di SMA Dharmawangsa Medan - Fauziah, Israhq; Faridah, Faridah (Kodifikasia, 2026)
Rohis activities in schools play an important role in shaping students' religious character, but there is still a gap between the potential role of Rohis and the low interest in worship and involvement of some students in religious activities. This indicates the importance of effective da'wah communication strategies in attracting student attention and participation. This study aims to analyze the influence of da'wah communication strategies on students' interest in worship and involvement in Rohis activities at Dharmawangsa High School, Medan. This study used a quantitative approach with a survey method by distributing questionnaires to 32 Rohis members selected using census techniques. Data were analyzed using linear regression and t-tests. The results showed that da'wah communication strategies significantly influenced students' interest in worship and involvement. The coefficient of determination showed that da'wah communication strategies contributed 86.4% to interest in worship and 57.8% to student involvement, while the remainder was influenced by other factors outside this study. These results confirm that effective, persuasive, and student-specific communication strategies can improve the quality of Rohis activities and provide practical implications for Rohis instructors and schools to design innovative, creative, interactive, and relevant approaches to the world of students.